Nanocellulose: Recent Fundamental Advances and Emerging Biological and Biomimicking Applications - Heise K; Kontturi E; Allahverdiyeva Y; Tammelin T; Linder M; Nonappa; Ikkala O (Wiley-VCH Verlag GmbH & Co. KGaA, 2022)
In the e'ort toward sustainable advanced functional materials, nanocellu- loses have attracted extensive recent attention. Nanocelluloses range from rod-like highly crystalline cellulose nanocrystals to longer and more entan- gled cellulose nanofibers, earlier denoted also as microfibrillated celluloses and bacterial cellulose. In recent years, they have spurred research toward a wide range of applications, ranging from nanocomposites, viscosity modi- fiers, films, barrier layers, fibers, structural color, gels, aerogels and foams, and energy applications, until filtering membranes, to name a few. Still, nanocelluloses continue to show surprisingly high challenges to master their interactions and tailorability to allow well-controlled assemblies for functional materials. Rather than trying to review the already extensive nanocellulose literature at large, here selected aspects of the recent progress are the focus. Water interactions, which are central for processing for the functional proper- ties, are discussed first. Then advanced hybrid gels toward (multi)stimuli responses, shape-memory materials, self-healing, adhesion and gluing, bio- logical sca'olding, and forensic applications are discussed. Finally, composite fibers are discussed, as well as nanocellulose as a strategy for improvement of photosynthesis-based chemicals production. In summary, selected per- spectives toward new directions for sustainable high-tech functional mate- rials science based on nanocelluloses are described.